2008
DOI: 10.1002/jcp.21451
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of Nav1.5: An electrophysiological comparison of ‘neonatal’ and ‘adult’ isoforms and critical involvement of a lysine residue

Abstract: In developmentally regulated D1:S3 splicing of Nav1.5, there are 31 nucleotide differences between the 5'-exon ('neonatal') and the 3'-exon ('adult') forms, resulting in 7 amino acid differences in D1:S3-S3/S4 linker. In particular, splicing replaces a conserved negative aspartate residue in the 'adult' with a positive lysine. Here, 'neonatal' and 'adult' Nav1.5 alpha-subunit splice variants were stably transfected into EBNA-293 cells and their electrophysiological properties investigated by whole-cell patch-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
112
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(133 citation statements)
references
References 52 publications
21
112
0
Order By: Relevance
“…Exon 6, located in the DI: S3 segment plays an important role in regulating development. The 5' neonatal isoform can be expressed at birth, while the 3' mature isoform is expressed later in development (37). Our study confirmed that the nNav1.5 Na + channel is widely expressed in rat CNS (9,28).…”
Section: Discussionsupporting
confidence: 80%
“…Exon 6, located in the DI: S3 segment plays an important role in regulating development. The 5' neonatal isoform can be expressed at birth, while the 3' mature isoform is expressed later in development (37). Our study confirmed that the nNav1.5 Na + channel is widely expressed in rat CNS (9,28).…”
Section: Discussionsupporting
confidence: 80%
“…Through studies in rat brain, it was possible to conclude that the transcription containing the 5' exon was more common at birth but was quickly replaced by the 3' exon. This splicing pattern has been found in studies with Nav1.1, Nav1.2, Nav1.3, Nav1.5, Nav1.6 and Nav1.7 (53 58). …”
Section: Voltage-gated Na+ Channelssupporting
confidence: 76%
“…The first involves simple posttranscriptional changes to the locus, such as RNA editing or alternative splicing (Liu et al, 2004;Onkal et al, 2008). However, our sequence of a nearly complete transcript reveals no such modifications.…”
Section: Discussionmentioning
confidence: 89%